Isolated expressive aphasia caused by acute subdural hematoma: case report and literature review - Stolevski, Vlado; Zdravkov, Ilija; Dimovski, Aleksandar (International Surgery Journal, 2024)
The occurrence of aphasia as an isolated and dominant clinical feature of acute subdural hematoma (aSDH) has been rarely mentioned in the available literature. Being the most common focal intracranial lesion, subdural hematomas (SDH) pose a clinical challenge, especially when presented with unorthodox clinical features. We report a case of a patient with a traumatic aSDH, presenting with intense frontal headaches and normal neurological examination. On the 3rd postadmission day, he developed expressive dysphasia which progressed to aphasia, with neurological examination findings of an upper motor neuron lesion (UMNL), without hematoma expansion, verified via head CT (computed tomography). The patient underwent decompressive craniotomy and hematoma evacuation. Early speech improvements were noted immediately postoperatively, and at hospital discharge the patient had no evident clinical features of speech disorder and neurological deficits or tests suggesting UMNL. Speech disorders in the setting of an aSDH need to be further investigated and potentially considered as an indication for surgical management, especially in rare instances where they present as an isolated clinical feature and conservative treatment is initially considered.